Pornography, the Internet and sexual offending - Bailey, Alexandra Jayne (2017)
This thesis focussed on online sexual offending, particularly the access of indecent images of children (IIOC), and whether certain risk factors associated with contact sexual offending, namely offence-supportive cognitions and deviant sexual interest (DSI), were relevant for individuals who access IIOC.